Activation of cannabinoid CB1 receptors suppresses HCN channels function in dorsal root ganglion neurons of rats - Xiaolu Lei; Meiyun Chen; Xingfeng Liu; Yan Yan; Xupeng Li; Fei Gong; Deqian Yu; Xiaohong Liu (Brain Research Bulletin)
Cannabinoid receptor (CBR) and hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are both critically involved in pain hypersensitivity induced by nerve injury. Both CBR and HCN channels are expressed in sensory neurons of the dorsal root ganglia (DRG). Studies have shown that HCN channel function is regulated by cAMP-PKA signaling, and the activation of cannabinoid receptor 1 (CB1R) can inhibit cAMP-PKA activity. However, it remains unclear whether the function of HCN channels is regulated by CB1R activity in DRG. In this study, we investigated the effect of ACEA, a selective agonist for CB1R, on HCN channel expression and function in the DRG of rats with chronic constriction injury (CCI) of the sciatic nerve. Mechanical allodynia was assessed by measuring the mechanical withdrawal threshold (MWT). HCN1/ HCN2 channel expression and cAMP level in lumbar 4, 5 and 6 (L4–6) DRG were detected by Western blot analysis and ELISA, respectively. As a result, MWT decreased significantly in CCI rats. HCN1/ HCN2 channel expression and cAMP level increased in the ipsilateral L4–6 DRG after CCI operation. Notably, intrathecal injection of ACEA (0.05 mg/kg) significantly decreased mechanical allodynia, HCN1/ HCN2 expression, and cAMP level in CCI rats, and this effect was blocked by the CB1R antagonist AM251. On the other hand, Ih mediated by HCN channels of DRG neurons was recorded by whole-cell patch-clamp to evaluate HCN channel activity. In this assay, ACEA (1 μM) significantly reduced the amplitude of Ih in DRG neurons (P < 0.01), while pretreatment with AM251 blocked the inhibitory effect of ACEA on Ih (P < 0.01). In addition, 8-Br-cAMP, a PKA activator, could reverse the effect of ACEA on Ih in DRG neurons (P < 0.01), indicating that CB1R activation suppresses the function of HCN channels by decreasing cAMP-PKA activity. In conclusion, these findings suggest that CB1R activation can inhibit the function of HCN channels by decreasing cAMP-PKA activity, resulting in decreased excitability of primary sensory neurons.